Символіка антропоморфних посудин олександрівської групи Трипілля А - Бурдо, Н.Б. (Материалы по археологии Северного Причерноморья, 2011)
Article is devoted to studies of the original category of Trypillya A ceramics — the anthropomorphous vessels, found at settlements of Olexandrivka group. Analysis of these data allows to think, that anthropomorphous ceramics belonged to wares, associated with sacral sphere. One can be given voice to supposition, that decoration of the anthropomorphous vessels possibly reproduced a Goddess figure. Signs symbols, to which the patterns saturated bordering this ceramics category, according with some of the elements of numerical encoding, probably connected with the Moon signs in different phases, and also snakes. Combination in one drawing of snake signs and Moon allows to suppose existence of conceptions about the sacral character of the Mooon Snake, which comes forward as attribute of the Moon Goddess. Decoration of anthropomorphous vessels possibly connected with some symbolical "sacral texts', which reflected fragments of myth, created by ancient farmers.